ANALISIS EFISIENSI PEMASARAN TELUR AYAM RAS DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN (STUDI KASUS PADA CV. XYZ) - Ni Nyoman Desmawati; Ani Suryani; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study aimed to analyze the marketing channels, margins, and marketing efficiency of layer chicken eggs at XYZ in Natar District, East Lampung Regency. By utilizing a case study method with both qualitative and quantitative descriptive analysis, the research measured the efficiency of layer chicken eggs by calculating the marketing margin, producer's share, and price transmission elasticity. This study involved 21 retailers, 5 wholesalers, and 9 collectors as respondents that selected by using a snowball sampling method. , to ensure that the selected traders were genuinely engaged in the marketing of purebred chicken eggs. The results identified three marketing channels: , 1) producer–retailer–consumer, 2) producer–collector–retailer–consumer, and 3) producer–collector–wholesaler–retailer–consumer. In each marketing channels, different marketing margins were formed across each marketing institution. Marketing channel I (producer–retailer–consumer) was the most efficient as it yielded the highest producer's share of 96%. Although all three channels were classified as efficient based on a producer's share exceeding 60%, the price transmission elasticity value of 1.17 indicated that the marketing system was not yet fully efficient due to imperfect price transmission mechanisms. In conclusion, shorter marketing chains would lead to higher efficiency and a larger price share for the producer.   Key words: chicken egg, margins, marketing channel, producer share